Correlation analysis of urban building form and PM2.5 pollution based on satellite and ground observations - Yu, Rui (Frontiers in Environmental Science, 2023)
Fine particulate matter (PM2.5) pollution is a key issue affecting the health of urban residents. To explore the impact of urban building form on PM2.5 pollution, this study focused on Wuhan, a Chinese megacity. Based on the urban building data, various building form indices were first calculated in grids to quantitatively present the spatial distribution of urban buildings. The city-scale PM2.5 distribution was obtained with satellite remote sensing and ground air pollution monitoring data. The impact of urban building forms on PM2.5 pollution distribution was then analyzed. The results show that the changes in PM2.5 concentration in Wuhan in the north–south direction have a relatively obvious correlation with the windward area ratio of buildings. The dense north–south buildings can slow the spread of near-surface particulate pollution. This finding demonstrates that the building blocking effect of PM2.5 diffusion in Wuhan is significant. The results of this study can provide a reference for urban planning, architectural design, and air pollution control strategies.